1998
DOI: 10.1161/01.str.29.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen in Acute Ischemic Stroke

Abstract: Background and Purpose-The effect of ebselen, a seleno-organic compound with antioxidant activity through a glutathione peroxidase-like action, on the outcome of acute ischemic stroke was evaluated in a multicenter, placebo-controlled, double-blind clinical trial. Methods-Patients diagnosed as having acute ischemic stroke who could receive drug treatment within 48 hours of stroke onset were enrolled. Oral administration of ebselen granules suspended in water (150 mg BID) or placebo was started immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
146
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(154 citation statements)
references
References 25 publications
2
146
0
6
Order By: Relevance
“…Ebselen has been studied as a potential agent to counteract some of the deleterious effects of ethanol. Studies demonstrate that ebselen protects the liver (39), gastric mucosa (37), CNS (40), and peripheral nerves from chronic alcohol exposure (41) by decreasing oxidative stress through inhibition of lipid peroxida- tion. Here, administration of ebselen results in a decrease in ethanol-induced cell death in the DG and particularly in protection of newly born neurons.…”
Section: Effects Of Ebselen On Neurogenesismentioning
confidence: 99%
“…Ebselen has been studied as a potential agent to counteract some of the deleterious effects of ethanol. Studies demonstrate that ebselen protects the liver (39), gastric mucosa (37), CNS (40), and peripheral nerves from chronic alcohol exposure (41) by decreasing oxidative stress through inhibition of lipid peroxida- tion. Here, administration of ebselen results in a decrease in ethanol-induced cell death in the DG and particularly in protection of newly born neurons.…”
Section: Effects Of Ebselen On Neurogenesismentioning
confidence: 99%
“…Because ebselen is effective against membrane hydroperoxides, it inhibits both nonenzymatic and enzymatic lipid peroxidation in cells and has anti-inflammatory activity in various animal models (5, 6). Ebselen also will directly inhibit inflammation-related enzymes such as 5-lipoxygenase, nitric oxide synthases, NADPH oxidase, protein kinase C, and ATPase by chemically modifying an SH-group forming a selenosulfide complex (5, 6).Because of its anti-inflammatory properties, ebselen has been used in the treatment of patients with acute ischemic stroke (7,8) or delayed neurological deficits after aneurysmal subarachnoid hemorrhage (9). The results of these clinical trials indicate the benefit of ebselen as a neuroprotective agent.…”
mentioning
confidence: 99%
“…Because of its anti-inflammatory properties, ebselen has been used in the treatment of patients with acute ischemic stroke (7,8) or delayed neurological deficits after aneurysmal subarachnoid hemorrhage (9). The results of these clinical trials indicate the benefit of ebselen as a neuroprotective agent.…”
mentioning
confidence: 99%
“…In more recent animal model studies, ebselen was shown to reduce oxidative stress in ischemiareperfusion in heart (10) and to have neuroprotective effects in brain (11)(12)(13)(14). More importantly, ebselen has been demonstrated to have beneficial effects in clinical trials for the treatment of patients with delayed neurological deficits after aneurysmal subarachnoid hemorrhage (15) and acute ischemic stroke (16,17).…”
mentioning
confidence: 99%